Laboratory Manual of Plant Pathology - and D. P. Thakur, N. N. Tripathi, Sushil Shanna (Indian Phytopathology, 2002)
This is the second edition of laboratory manual which deals with the important plant pathogens. The book is meant for undergraduate students. The authors have given important characters of the pathogens with the help of line  drawings which are below standard. Some of the glaring points which are omitted by the authors are in Excercise 10, no foot cell has been drawn and the ascospores in the cleistothccium .do not resemble with any member of Aspergillus. The  terminology bottle, biscuit shaped should not be used  (Exercise 10 and 11) because this will lead to confusion. The perfect state of Penicillia are Eupenicillium, Talaromyces etc. and never called as Eurotium as mentioned in the book. The latest name of Tolyposporium penicillariae has changed to Moeziomyces penicilliarae which should be used. There is an irritating sprinkling of typographical errors in the book, but this does not detract from the usefulness of the work. As for price, J feel it is well within the reach of the students who need it quite often in their practical classes. The  authors have added one more chapter dealing with 'Fungicides' it is really a welcome addition in the book.